Determining the role and responsibilities of the Australian epilepsy nurse in the management of epilepsy: a study protocol. Issue 1 (25th January 2021) - Rapport, Frances; Hutchinson, Karen; Herkes, Geoffrey K; Bleasel, Andrew; Nikpour, Armin; Ryder, Tayhla; Wong, Chong; Bartley, Melissa; Ireland, Carol; Coleman, Honor; Todd, Lisa; Groot, Wendy; et al.
Abstract : Introduction: Epilepsy is a common neurological condition affecting between 3% and 3.5% of the Australian population at some point in their lifetime. The effective management of chronic and complex conditions such as epilepsy requires person-centred and coordinated care across sectors, from primary to tertiary healthcare. Internationally, epilepsy nurse specialists are frequently identified as playing a vital role in improving the integration of epilepsy care and enhancing patient self-management. This workforce has not been the focus of research in Australia to date. Methods and analysis: This multistage mixed-method study examines the role and responsibilities of epilepsy nurses, particularly in primary and community care settings, across Australia, including through the provision of a nurse helpline service. A nationwide sample of 30 epilepsy nurses will be purposively recruited via advertisements distributed by epilepsy organisations and through word-of-mouth snowball sampling. Two stages (1 and 3) consist of a demographic questionnaire and semistructured interviews (individual or group) with epilepsy nurse participants, with the thematic data analysis from this work informing the areas for focus in stage 3. Stage 2 comprises of a retrospective descriptive analysis of phone call data from Epilepsy Action Australia's National Epilepsy Line service to identify types of users, their needs and reasons for using the service, and to characterise the range of activities undertaken by the nurse call takers. Ethics and dissemination: Ethics approval for this study was granted by Macquarie University (HREC: 52020668117612). Findings of the study will be published through peer-reviewed journal articles and summary reports to key stakeholders, and disseminated through public forums and academic conference presentations. Study findings will also be communicated to people living with epilepsy and families.